Inaugural Address (The Pakistan Development Review, 1998)
It is gratifying to know that the Pakistan Society of Development Economists established in 1982 as a forum to discuss economic issues of national and international interest to Pakistan has successfully completed 16 years of fruitful work. Its deliberations have also made a useful contribution to policy formulation in Pakistan. The Society has made possible a meaningful exchange of ideas and experiences amongst academics, researchers, and policy-makers. The current meeting of the society is taking place at a time when the global economy is passing through a crucial stage of its history. The current year is the terminal year of the 20th century and provides a bridge between the last and the next millennium; it is a time to reflect on our past achievements and failures, and against this backdrop, chart out our course for the future.